Nanomolar detection of mercury(II) using electropolymerized phthalocyanine film. (20th January 2021) - Palanna, Manjunatha; Aralekallu, Shambhulinga; Keshavananda Prabhu, CP; Sajjan, Veeresh A; Mounesh,; Sannegowda, Lokesh Koodlur
Highlights: Novel substituted benzimidazole phthalocyanine is synthesized via cyclization and coupling reaction. Benzimidazole phthalocyanine was electropolymerized to obtain thin, uniform film on the electrode and characterized. CV and amperometric methods showed distinct linear response in nanomolar range with a lower LOD for Hg (II). Practical applicability of sensor is assessed by real sample analysis, interference studies, reproducibility and stability tests. Abstract: The synthesis and characterization of novel cobalt(II) tetraamide benzimidazole phthalocyanine (CoTABImPc) has been reported for the first time and applied for the determination of mercury(II) at nanomolar concentration using electrochemical techniques. CoTABImPc was prepared by coupling 4-(1H-benzimidazol-2-yl)aniline with cobalt(II) tetracarboxylic acid phthalocyanine. CoTABImPc was characterized by elemental analysis, TGA, FT-IR, UV–visible, Mass, and NMR spectroscopic techniques. The CoTABImPc was electropolymerized on clean glassy carbon electrode (GCE) by continuous cycling of the potential (GCE/poly(CoTABImPc)). The polymeric film was employed for the detection of highly toxic Hg(II) by cyclic voltammetry (CV), differential pulse voltammetry (DPV) and chronoamperometric (CA) methods. The designed GCE/poly(CoTABImPc) electrode exhibited good electrochemical response and high electrocatalytic activity for detecting Hg(II). The Pc polymeric film electrode displayed a sensitivity of 1.2178 µA nM −1 cm −2 for the detection of Hg(II) in the linear range 10–300 nM, and low detection limit of 4 nM using CV technique. Further, DPV exhibited a sensitivity of 1.4024 µA nM −1 cm −2 in the 10–500 nM range with LOD of 3.8 nM. The CA method delivered an excellent sensitivity of 3.7389 µA nM −1 cm −2 in the linear range 10–400 nM with LOD of 3 nM. The proposed method augments the selective electrochemical determination of Hg(II) in environment pollution analysis.